Legal documents as sources for the history of Muslim societies : studies in honour of Rudolph Peters - Peters, Rudolph.; Berkel, Maaike van.; Buskens, Léon, 1962-; Sijpesteijn, Petra. (Studies in Islamic Law and Society, 2017)
This volume is a tribute to the work of legal and social historian and Arabist Rudolph Peters (University of Amsterdam). Presenting case studies from different periods and areas of the Muslim world, the book examines the use of legal documents for the study of the history of Muslim societies. From examinations of the conceptual status of legal documents to comparative studies of the development of legal formulae and the socio-economic or political historical information documents contain, the aim is to approach legal documents as specialised texts belonging to a specific social domain, while simultaneously connecting them to other historical sources. It discusses the daily functioning of legal institutions, the reflections of regime changes on legal documentation, daily life, and the materiality of legal documents. Contributors are Maaike van Berkel, Maurits H. van den Boogert, Léon Buskens, Khaled Fahmy, Aharon Layish, Sergio Carro Martín, Brinkley Messick, Toru Miura, Christian Müller, Petra M. Sijpesteijn, Mathieu Tillier, and Amalia Zomeño.